2020
DOI: 10.1186/s13765-020-00510-4
|View full text |Cite
|
Sign up to set email alerts
|

Influence of light-emitting diodes on phenylpropanoid biosynthetic gene expression and phenylpropanoid accumulation in Agastache rugosa

Abstract: Agsatache rugosa (Korean mint), belongs to the mint family and it has various medicinal properties. In addition, it has several valuable compounds such as monoterpenes and phenylpropanoid compounds. Amongst these, two compounds viz., rosmarinic acid (RA), and tilianin are well-known natural compounds that have numerous pharmacological properties. The phenylpropanoid biosynthetic gene expression under stress conditions and the subsequent accumulation of phenylpropanoid content has not been extensively studied i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 41 publications
2
22
1
Order By: Relevance
“…Numerous previous studies have reported that LED illumination can enhance secondary metabolite production in vegetables and medicinal plants. White LED illumination has been shown to increase the accumulation of phenolics in Agastache rugosa seedlings [16], carotenoids in Fagopyrum tataricum sprouts [17], and glucosinolates in Brassica juncea sprouts [11], compared with other colored LED lights, consistent with the findings of this study. Blue LED light has been reported to increase accumulations of phenolics in Brassica napus [18] and Glycine max sprouts [19], and red LED light has been shown to enhance both phenolic compounds in the leaves of Myrtus communis in vitro [20] and carotenoid production in the outer peel layer of citrus fruit [21].…”
Section: Discussionsupporting
confidence: 90%
“…Numerous previous studies have reported that LED illumination can enhance secondary metabolite production in vegetables and medicinal plants. White LED illumination has been shown to increase the accumulation of phenolics in Agastache rugosa seedlings [16], carotenoids in Fagopyrum tataricum sprouts [17], and glucosinolates in Brassica juncea sprouts [11], compared with other colored LED lights, consistent with the findings of this study. Blue LED light has been reported to increase accumulations of phenolics in Brassica napus [18] and Glycine max sprouts [19], and red LED light has been shown to enhance both phenolic compounds in the leaves of Myrtus communis in vitro [20] and carotenoid production in the outer peel layer of citrus fruit [21].…”
Section: Discussionsupporting
confidence: 90%
“…In another study, a positive correlation between anthocyanin accumulation and flavonoid synthesis-related gene expression, including that of 4-coumaryol CoA-ligase (4CL) and phenylalanine ammonia synthase, was observed in Cyclocarya paliurus grown under blue LED irradiation [ 57 ]. Park et al [ 72 ] reported an increase in the levels of rosmaric acid, tilianin, and expression of genes encoding phenylpropanoid biosynthesis-related enzymes, such as cinnamate 4-hydroxylase (C4H), chalcone isomerase (CHI), and RAS, in Acaulospora rugosa under white LED irradiation, compared with irradiation with other LEDs. Similarly, enhanced gallic acid and quercetin accumulation and decreased p -coumaric acid and epicatechin levels were observed in wheat sprouts grown under blue LED irradiation [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Other studies have reported increased TPC in Chinese cabbage and lettuce irradiated with blue LEDs alone compared with those irradiated with red LEDs alone or a combination of red and blue LEDs [ 98 ], indicating that the effects of LEDs on TPC varied among plant species. Several studies have investigated the levels of phenolic compounds in plant species grown under LED irradiation [ 55 , 57 , 58 , 68 , 72 , 174 , 175 ]. Chung et al [ 4 ] reported an increase in malonyldaidzin, malonyl genistin, salicylic acid, p -hydrobenzoic acid, and gentisic acid levels in Pachyrhizus erosus grown under red LED irradiation.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, a significant increase in the level of chlorogenic acid was observed in red + blue LED-treated eggplant. The increase in bioactive compounds in red + blue LED-exposed eggplants is probably caused by the stimulation of genes, owing to the phenylpropanoid pathway, which is related to the biosynthesis of phenolic acids and flavonoid content in plants [8,28]. The other explanation for the higher antioxidant activity of plants exposed to blue LEDs is that the higher energy levels of short wavelengths (blue at 450-460 nm for example) stimulate oxidative stress, thus enhancing the scavenging of reactive oxygen species [16].…”
Section: Discussionmentioning
confidence: 99%